"ONE\\\\1.\\; 3(2x + 11) = 9; first\\ we \\;open\\ the\\ brackets\\\\ to\\ do\\ this\\ we\\ multiply\\ each\\ term\\\\ in\\ the\\ brackets\\ by\\ a \\;common \\;multiplier\\\\2.\\;6x + 33 = 9 ;\\;each\\ term\\ enclosed\\ in\\\\ parentheses\\\\ must\\ be\\ multiplied\\ by\\ a\\ common\\ factor.\\\\3.\\;6x=-24;\\;move\\ the \\;known\\ term\\ to\\ the\\\\ right\\ by\\ changing \\ the \\;plus\\ sign\\ to\\ minus.\\\\4.\\;x=-4; divide\\ the\\ right\\ and\\\\ left\\ sides\\ of\\ the\\ equation\\ by\\;6\\\\the \\;solution\\\\ of\\ the \\;equation\\;is\\ finished\\\\TWO\\\\44 - 2(3x + 4) = -18x;\\ we \\;open\\ the\\ brackets\\\\ to\\ do\\ this\\ we\\ multiply\\ each\\ term\\\\ in\\ the\\ brackets\\ by\\ a \\;common \\;multiplier\\\\\n44 - 6x - 8 = -18x;now\\ we\\ subtract\\ 8 from\\ 44 \\\\ \n-6x + 36 = -18x \\\\and \\;move\\ the\\ unknown\\\\ quantity\\ to\\ the\\ right\\\\ while\\ subtracting\\\\\n36 = -12x\\\\ divide\\ the\\ right\\ and\\\\ left\\ sides\\ of\\ the\\ equation\\ by\\;12\\\\\n-3 = x;changing \\;the\\ right\\ part\\ to\\ the\\ left \\\\x=-3 ; that\\ is\\ all"
Comments
Leave a comment